2018
DOI: 10.1111/neup.12485
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase IX is a prognostic biomarker in glioblastoma multiforme

Abstract: The identification of prognostic factors in patients with glioblastoma multiforme (GBM) represents an area of increasing interest. Carbonic anhydrase IX (CA-IX), a hypoxia marker, correlates with tumor progression in a variety of human cancers. However, the role of CA-IX in GBM remains largely unknown. In the present study, we evaluated the prognostic role of CA-IX in GBM patients. In total, 66 consecutive patients with GBM who received concomitant chemoradiotherapy and adjuvant chemotherapy with temozolomide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Since glioblastomas are highly hypoxic tumours and the expression of hypoxia markers correlates with a worse prognosis [40–42], we determined whether tetraspanin profiles of glioblastoma cells and corresponding EVs are altered by hypoxia. Three different glioblastoma cell lines (GS‐8, GS‐57, BT112) were incubated under hypoxic conditions (0.1% O 2 ), and for comparison also under differentiating conditions (medium containing FBS).…”
Section: Resultsmentioning
confidence: 99%
“…Since glioblastomas are highly hypoxic tumours and the expression of hypoxia markers correlates with a worse prognosis [40–42], we determined whether tetraspanin profiles of glioblastoma cells and corresponding EVs are altered by hypoxia. Three different glioblastoma cell lines (GS‐8, GS‐57, BT112) were incubated under hypoxic conditions (0.1% O 2 ), and for comparison also under differentiating conditions (medium containing FBS).…”
Section: Resultsmentioning
confidence: 99%
“…In other cancer types, including breast carcinoma, hepatocellular carcinoma, cervical carcinoma and renal cell carcinoma, CAIX expression is associated with poor prognosis. [33][34][35][36][37] More specifically, increased distant failure was seen in several solid tumour types with positive CAIX expression. 37,38 The metastatic process is a complex step-wise process, including acquisition of an aggressive phenotype, invasion in surrounding tissues and blood vessels, survival in the circulation with subsequent extravasation and colonisation in new organs.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Cetin and coworkers verified the finding of prognostic value of CA IX in glioblastomas and showed that the median overall survival was longer in patients with low levels of CA IX expression (18 months) compared to patients with CA IX overexpression (9 months) [ 58 ]. In multivariate analysis, significant prognosticators included CA IX overexpression, Karnofsky performance scale, incomplete temozolomide treatment, and gross-total resection.…”
Section: Cas In Brain Tumorsmentioning
confidence: 95%